If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-6=2-2x
We move all terms to the left:
6x-6-(2-2x)=0
We add all the numbers together, and all the variables
6x-(-2x+2)-6=0
We get rid of parentheses
6x+2x-2-6=0
We add all the numbers together, and all the variables
8x-8=0
We move all terms containing x to the left, all other terms to the right
8x=8
x=8/8
x=1
| 9x-8/4=11 | | (6×+5y)=(3×+2y) | | 10+7x+4x=16 | | 54-u=251 | | NxN=225 | | 12y+6=6=6(2y+1) | | 9+3x+x=49 | | 6(x−2)=−48# | | 99=22+35c | | 4/5x=27 | | 13=21t-8 | | 90+5x-5=180 | | 5x-11=4-x | | 10^2t=122 | | 2y7=9 | | 4x=3(x+45) | | 1/5a+2/3=1/3a-2/3 | | 4=8^x | | 6+5x+3x=86 | | 1664=2^x | | 2+2x+3x=62 | | 11x2-5x=0 | | 10x+3=8x+17 | | 6z–z=10 | | 3+x=16/5 | | 31-3y=1-(-3+6y) | | 3+7x=33/4 | | 4/5x-4=2/3x | | 31-3y=1-(-3=6y) | | 5m+5=40m= | | y=2000(1.02)^315000 | | 5y2-64y+220=0 |